Evaluating impacts of road expansion on porcupines in a biodiversity hotspot. (January 2022) - Secco, Helio; da Costa, Vitor Oliveira; Guerreiro, Marcello; Gonçalves, Pablo Rodrigues
Abstract: The improvement of transportation networks by road twinning is a major trend worldwide, but also brings possible threats to wildlife that have not been thoroughly assessed. The present study aims to evaluate how the changes in structural characteristics during road twinning affect roadkill rates of dwarf hairy porcupines ( Coendou spinosus ) in the southeast portion of the Brazilian Atlantic Forest, a major world biodiversity hotspot. The dataset for this study comes from monthly monitoring campaigns, carried out between 2013 and 2018, in the BR-101/RJ Norte (km 84–124), a major highway located in Rio de Janeiro state. The influences of structural modifications by road twinning (number of lanes, presence of road barrier, traffic, presence of construction operations, number of native vegetation on both margins of the road, sampling period) in the species roadkill rates were evaluated by means of generalized linear mixed effects models (GLMMs) selected based on an information theoretical approach. The average roadkill rate was 0.015 porcupine individuals/km/day of sampling and presented a trend of increase during the expansion works and decrease after the conclusion of road twinning and lane widening. Model averaging showed that presence of Jersey barriers, number of lanes, construction works for twinning, and traffic were the most influential variables for roadkill rate. An emergency measure to minimize the impact of Jersey barriers could be the implementation of escape mechanisms alongside Jersey blocks that could enable animals to cross the divider. We also propose other mitigation measures, such as the installation protective fences and safe passages, and draw insights into the behavioural responses of porcupines to roads and traffic.